Evaluation of the risk of hepatic fibrosis in the preoperative period of bariatric surgery using the Fibrosis-4 score (FIB-4): A retrospective observational analysis (Research, Society and Development, 2025)
Introduction: Hepatic fibrosis is a common complication in individuals with obesity and nonalcoholic fatty liver disease (NAFLD), increasing the risk of morbidity and mortality in bariatric surgery. The FIB-4 index, based on simple laboratory parameters, has been proposed as a noninvasive tool to estimate the degree of fibrosis. Objective: To evaluate the performance of the FIB-4 score in predicting hepatic fibrosis in candidates for bariatric surgery with hepatic steatosis. Methods: Retrospective observational study (2015–2023) including 618 patients aged ≥18 years with confirmed steatosis and preoperative laboratory tests. The FIB-4 was calculated and compared with histopathological examination (gold standard). Analyses included multivariable logistic regression and ROC curve. Results: The cohort had a mean age of 38.9 ± 10.2 years and a predominance of females (75.2%). A FIB-4 cutoff ≥ 1.3 was significantly associated with histological fibrosis (OR 21.87; 95%CI 10.92–43.79; p